Measuring Well-Being in Israel and Palestine: The Subjective Well-Being Assessment Scale. Issue 6 (December 2017) - Veronese, Guido; Pepe, Alessandro; Dagdouke, Jamal; Addimando, Loredana; Yagi, Shaher
This work presents the psychometric properties of the Subjective Well-Being Assessment Scale in a sample of 423 participants composed of Israeli Arabs and Palestinians from the West Bank/Gaza Strip. Psychometric assessment of the instrument was based on confirmatory factor analysis. The convergent and discriminant validity of Subjective Well-Being Assessment Scale were also tested via administration of the General Health Questionnaire and the Positive and Negative Affect Scale . The results suggest that Subjective Well-Being Assessment Scale is valid, reliable, and solid from a psychometric point of view and provides an accurate assessment of respondents' well-being. The questionnaire is therefore recommended for practical use in the psychological and health-care fields, whether locally or in international contexts with migrants and refugees from Arabic-speaking countries.